To solve for m, we need to isolate the variable on one side of the equation.
m - 2/12 = 1/6
First, we need to simplify the fractions on both sides:
m - 1/6 = 1/6 (2/12 can be simplified to 1/6)
Next, we can eliminate the fraction on the left side by adding 1/6 to both sides:
m - 1/6 + 1/6 = 1/6 + 1/6
Simplifying further:
m = 2/6
And finally, we can simplify 2/6 to 1/3:
m = 1/3
Therefore, the solution is m = 1/3.
Solve m-2/12=1/6 .
2 answers
I have a feeling the poster meant:
(m - 2)/12 = 1/6
m - 2 = 12/6
m - 2 = 2
m = 4
(m - 2)/12 = 1/6
m - 2 = 12/6
m - 2 = 2
m = 4